Implementing a STEAM-Based Flipped Learning Model to Improve Student Understanding of Trigonometry: An Analysis of Effectiveness and Challenges - Naufal Ishartono; Hety Dwi Agus Setyaningrum; Fayza Putri Chalistha; Retno Palupi (Mathematics Education Journal, 2026)
Limited exploration of the integration of the STEAM approach within the flipped learning framework for trigonometric instruction, particularly concerning its pedagogical efficacy and the challenges inherent in its implementation, creates a prominent gap in existing literature. Furthermore, there is a paucity of comprehensive research that identifies the multidimensional obstacles students face when grappling with the abstract nature of the subject matter. Therefore, this study aimed to assess the effectiveness of a STEAM-based flipped learning model in enhancing students’ conceptual understanding of trigonometry and to delineate barriers encountered during its implementation. Methodologically, the research took an explanatory sequential mixed-methods approach, utilizing a quasi-experimental pretest-posttest control group design, with three distinct sample groups, followed by a thematic analysis of in-depth interviews with students exhibiting lower prior academic achievement. The quantitative findings demonstrate that the STEAM-based flipped learning model yielded a statistically significant improvement in students' conceptual understanding relative to comparative models. Complementary to these results, qualitative data shed light on critical implementation challenges, with specific emphasis on the prerequisite for initial technological training and the demand for effective time management for project fulfillment. Ultimately, this study offers an integrated solution framework to assist educators in optimizing hybrid learning strategies for abstract content, while simultaneously enriching theoretical discourse through a five-dimensional chain effect analysis.